Pengembangan E-module Materi Persamaan Nirlanjar dengan Pendekatan Konstruktivisme Berbantuan Microsoft Excel - Fitriasari, Putri; Ningsih, Yunika Lestaria (Edumatica : Jurnal Pendidikan Matematika, 2021)
This study aims to produce a valid and practical e-module of the Non-linear Equation with a Microsoft Excel-assisted constructivism approach for students. This research is development research using the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. Data in this study were collected through questionnaires, documentation, and interviews. Data in this study were analyzed descriptively qualitatively and quantitatively. The result of this research is that the e-module of the Non-linear Equation with a Microsoft Excel-assisted constructivism approach is valid and feasible for students. The validity of the e-module is seen from the results of experts' assessments of the material and media used in the e-module. The overall e-module validity score was 83.5%. The feasible of e-module can be seen from the results of student responses who use e-module in learning the Non-linear Equation. The result of student response is 90.16% with a very good practicality category. Based on the results and data analysis, it can be concluded that the developed e-module is valid and feasible so that it can be used in learning the Non-liniear Equation.